The Impact Of Cyberbullying On Adolescents On Social Media - Romy Maranatha Ginting; Muhammad Arif Sahlepi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The development of social media networks is extraordinary, with very easy access and unlimited friendships so that all groups regardless of social status ranging from old, young, and even children are so enthusiastic in using social media especially teenagers. Social networks are also used as a place for emotional outbursts, and it is not uncommon to express anger in the form of insults or insults which are often referred to as cyberbullying. The ITE Law provides legal protection for victims of criminal acts of cyberbullying as an effort to protect the law which is interpreted as the recognition and guarantees provided by the law in relation to human rights. Legal protection is a